A contribution to the knowledge of the bryophytes of the Cape Verde Islands, with an emphasis on Santo Antão and São Vicente. (3rd April 2021) - Garcia, César Augusto; Sérgio, Cecília; Martins, Anabela; Rodrigues, Ana S. B.; Sim-Sim, Manuela
Abstract : Introduction: The Cape Verdean bryophyte flora comprises representatives of various floristic elements including Afrotropical, Neotropical, Mediterranean and Asiatic elements, together with some endemic taxa. However, the knowledge of Cape Verdean bryophytes lags far behind that of vascular plants. Methods: A total of seven sites were sampled during 2016 in the Cape Verde archipelago, one on São Vicente and six on Santo Antão. Results and conclusions: Five species are reported new to Cape Verde, Cheilolejeunea rigidula (Nees ex Mont.) R.M.Schust., Riccia trabutiana Steph., Lewinskya acuminata (H.Philib.) F.Lara, Garilleti & Goffinet, Lindbergia patentifolia Dixon and Timmiella cameruniae Broth. The presence of Porella canariensis (F.Weber) Underw in the archipelago is also confirmed. Additionally, Frullania spongiosa Steph., Bryum dichotomum Hedw., Cryptoleptodon longisetus (Mont.) Enroth and Didymodon hastatus (Mitt.) R.H.Zander are reported for the first time from Santo Antão. Cheilolejeunea rigidula, Lindbergia patentifolia and Timmiella cameruniae are new to Macaronesia and a description of the last taxon is presented.